2012
DOI: 10.5213/inj.2012.16.4.181
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin Resistance with Overactive Bladder in Female Patients

Abstract: PurposeMetabolic syndrome and obesity have been advocated to be risk factors for the development of overactive bladder (OAB). Additionally, insulin resistance is the underlying mechanism of metabolic syndrome. We aimed to investigate the association of insulin resistance with overactive bladder in female patients.MethodsWe prospectively conducted the study in our urology department. Female patients aged between 30 and 76 years old applied to our policlinics with or without OAB symptoms were enrolled. One hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
3
19
0
1
Order By: Relevance
“…An overview of the selection process can be seen in Figure . Two studies were classified as case–control studies and the rest as surveys/cross‐sectional studies. The number of participants in studies ranged from 60 to 27,936.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An overview of the selection process can be seen in Figure . Two studies were classified as case–control studies and the rest as surveys/cross‐sectional studies. The number of participants in studies ranged from 60 to 27,936.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies made a specific reference to OAB . The others categorised urinary symptoms in a variety of ways including LUTS, UUI, SUI and MUI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed a relationship between MetS and OAB [5,10,11] and their pathogeneses have many factors in common. For example, visceral obesity, aging, high body mass index, hypertension and increased HOMA-IR values have all been associated with both OAB and MetS [5,12]. Furthermore, MetS may contribute to sympathetic overactivity, causing detrusor overactivity and the activation of sensory neurons that secrete inflammatory mediators [13].…”
Section: Discussionmentioning
confidence: 99%
“…Women with obstetric history including complicated labour followed by continuous UI are suggestive of a istula. A detailed gynaecological history may help to understand the underlying cause, for example, polycystic ovarian disease and associated insulin resistance leading to UI among women of younger age group [7].…”
Section: History and Physical Examinationmentioning
confidence: 99%